DIVERSIFIKASI RASA DAN KEMASAN KRUPUK PARU UNTUK MENINGKATKAN PENJUALAN - Fatmawati Fatmawati; Henny Diana Wati; Yayuk Sugiarti (LPPM Universitas Wiraraja Sumenep, Jalan Raya Sumenep Pamekasan KM. 5 Patean Sumenep 69451, Telp. (0328) 673399 Fax. (0328) 673088, 2018)
Utilization of cattle lungs is not only served in the form of side dishes or lung empal. But in the hands of Yasmin women groups located in Kacongan Village and violet women groups located in Parsanga Village, cow lungs are transformed into savory and high economic value snacks so they can provide income in the family. These crackers are not only tasty and of high economic value, but also contain high protein which is very beneficial for the body. This is because protein is essential to play a role in the growth and formation of body tissues. Expected outputs are as follows: (1) The creation of a distinctive taste of cow's lung crackers, which is spicy and cheese-flavored, (2) The packaging of cow lung crackers that is more interesting and unique, (3) Making brands of cow lung crackers produced, and (4) Increased sales of cow lung crackers. The results of the activities showed the enthusiasm of the participants, so this indicated that this activity was exciting.